2011
DOI: 10.1007/s13280-011-0188-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dust Filter Installation in Ironworks and Construction on Brownfield Area on the Toxic Metal Concentration in Street and House Dust (Celje, Slovenia)

Abstract: This article presents the impact of the ecological investment in ironworks (dust filter installation) and construction works at a highly contaminated brownfield site on the chemical composition of household dust (HD) and street sediment (SS) in Celje, Slovenia. The evaluation is based on two sampling campaigns: the first was undertaken 1 month before the ecological investment became operational and the second 3 years later. The results show that dust filter installations reduced the content of Co, Cr, Fe, Mn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…In all cases, indoor dust Mn levels were significantly lower than outdoor levels, with the median indoor/outdoor dust Mn concentration ratios ranging from 0.15 (Bagnolo Mella) to 0.33 (Valcamonica) to 0.44 (Garda Lake). The differences between indoor and outdoor dust Mn concentrations in Valcamonica and Garda Lake are similar to values of Tong et al (Tong et al, 1998), who reported mean indoor dust Mn levels (224 µg/g) from schools in Hong Kong that were ~40% of outdoor dust Mn levels (532 µg/g), and Zibret et al (Zibret et al, 2012) who reported indoor house dust Mn levels that were ~45% of outdoor levels in the vicinity of a ferroalloy plant in Solvenia (Table 3). …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In all cases, indoor dust Mn levels were significantly lower than outdoor levels, with the median indoor/outdoor dust Mn concentration ratios ranging from 0.15 (Bagnolo Mella) to 0.33 (Valcamonica) to 0.44 (Garda Lake). The differences between indoor and outdoor dust Mn concentrations in Valcamonica and Garda Lake are similar to values of Tong et al (Tong et al, 1998), who reported mean indoor dust Mn levels (224 µg/g) from schools in Hong Kong that were ~40% of outdoor dust Mn levels (532 µg/g), and Zibret et al (Zibret et al, 2012) who reported indoor house dust Mn levels that were ~45% of outdoor levels in the vicinity of a ferroalloy plant in Solvenia (Table 3). …”
Section: Discussionsupporting
confidence: 87%
“…Notably, that study also reported a significant inverse relationship between dust Mn levels and distance from the steel plant, as we observed in Bagnolo Mella. (Zibret et al, 2013) Separately, a study by Zibret et al, (Zibret et al, 2012) reported outdoor dust Mn levels of 2970 µg/g in the vicinity of a ferroalloy plant in Celje, Slovenia, where levels declined by half to 1310 µg/g following installation of emission control filters on the plant. These data show that, in general, active ferromanganese alloy plant operations significantly impact the local dust Mn levels.…”
Section: Discussionmentioning
confidence: 99%
“…Since XRF-measured Cr was not accurate and no XRF measurement of Cd was higher than the detection limit, XRF measurements of Cr and Cd were abandoned and only ICP measurements of these two elements were used in further analysis. Although 50 % of the detection limit may be used as the substitution in cases where concentrations were BDLs (Zibret 2012), taking this substitution into account would bring about big errors when establishing regression models and performing the transformations. Therefore, in the data transformation stage, ICP measurements of Pb, Zn, Cu, Cr, and Cd were reserved at the training sample points, and XRF measurements of Pb, Zn, and Cu that were higher than detection limit were transformed using the regression models at other data points.…”
Section: Appendix 2: Xrf Data Transformationmentioning
confidence: 99%
“…On the one hand, soil particles can enter the atmosphere as dusts, being further carried by wind into sensitive environments (Meza-Figueroa et al 2007). These dusts mainly come from urban construction sites (Zibret 2012) and vehicular exhaust (Johansson et al 2009). On the other hand, contaminated urban soils may also affect water quality due to surface runoff and soil erosion (Helmreich et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Attic dust is derived predominantly from external sources such as aerosol deposits and as a result of crop dusting and less from household activities (Šajn 1999, 2003). Attic dust as sampling material has the advantage that its composition remains constant, i.e., chemically unchanged over time, as long as the anthropogenic source of pollution is not changed; otherwise, it changes over time (Žibret and Rokavec 2010;Žibret 2012). Investigations of attic dust chemistry therefore reveal the average historical state of the atmosphere (Šajn 1999, 2000, 2005Balabanova et al 2011;Bačeva et al 2011;Stafilov et al 2012).…”
Section: Introductionmentioning
confidence: 99%